Effect of Cu addition on antibacterial property of type 200 stainless steel. (2nd January 2016) - Nan, L.; Yang, K.
Abstract : Effect of Cu addition (1·45–3·57 wt-%) on the antibacterial property of a type 200 austenitic stainless steel was investigated by ways of direct plate counting, epifluorescence microscope and scanning electron microscope. The results showed that with increase in the Cu content, the antibacterial rates of the steel against Escherichia coli and Staphylococcus aureus were both enhanced, reaching over 90·0% on 2·77%Cu. This novel Cu bearing stainless steel not only killed large amount of planktonic bacteria around its surroundings but also effectively inhibited the biofilm formation on its surfaces. Variations of bacterial morphologies further demonstrated that the Cu bearing stainless steel inactivated the bacteria and damaged the cell walls, thus leading to the death of bacteria.